잡 크래프팅 모델에 근거한 아동간호사의 직무열의 구조모형 - 강정미; 조헌하; Kang, Jung Mi; Cho, Hun Ha (Child health nursing research, 2020)
Purpose: The goal of this study was to construct a structural equation model of job engagement in pediatric nurses based on Tims and Bakker's job crafting model. Methods: In total, 203 pediatric nurses participated in this study, which was conducted to analyze the relationships among the concepts of job demands, job resources, person-job fit, job crafting and job engagement. Data were collected from July 24 to August 30, 2017, and analyzed using SPSS 20.0 and AMOS 21.0. Results: The hypothetical model appeared to fit the data. Six of the nine hypotheses selected for the hypothetical model were statistically significant. The job engagement model showed significant direct effects for job crafting, person-job fit and job resources, which collectively explained 61.5% of the variation in pediatric nurses' job engagement. Conclusion: Based on the findings of this study, a strategy will be needed to improve job resources and person-job fit in order to promote job engagement among pediatric nurses. Job crafting was affected by the factors of job resources and person-job fit, which should be addressed in job crafting promotion programs.